2019
DOI: 10.1111/rec.12962
|View full text |Cite
|
Sign up to set email alerts
|

Microbial inoculation influences arbuscular mycorrhizal fungi community structure and nutrient dynamics in temperate tree restoration

Abstract: Soil microbial communities have a profound influence on soil chemical processes and subsequently influence tree nutrition and growth. This study examined how the addition of a commercial inoculum or forest‐collected soils influenced nitrogen (N) and phosphorus (P) dynamics, soil microbial community structure, and growth in Liriodendron tulipifera and Prunus serotina tree saplings. Inoculation method was an important determinant of arbuscular mycorrhizal fungi (AMF) community structure in both species and alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 51 publications
(70 reference statements)
1
9
0
Order By: Relevance
“…We found a significant influence of inoculation of rhizosphere fungal community structure in Liriodendron and a weakly significant influence in Quercus; Prunus rhizosphere fungal community structure, however, did not differ between soil treatments. Species‐specific responses to inoculation have been noted previously in temperate trees (St Denis et al ; Lance et al ) and our current study provides further evidence that broadly applicable inoculation protocols are unlikely to be easily developed. Species‐specific inocula, which could be developed using HTS technologies, may result in the best tree growth and performance in restoration contexts.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We found a significant influence of inoculation of rhizosphere fungal community structure in Liriodendron and a weakly significant influence in Quercus; Prunus rhizosphere fungal community structure, however, did not differ between soil treatments. Species‐specific responses to inoculation have been noted previously in temperate trees (St Denis et al ; Lance et al ) and our current study provides further evidence that broadly applicable inoculation protocols are unlikely to be easily developed. Species‐specific inocula, which could be developed using HTS technologies, may result in the best tree growth and performance in restoration contexts.…”
Section: Discussionsupporting
confidence: 73%
“…Our hypotheses were that the inoculation method would lead to distinct fungal community structure and that soil samples from trees inoculated with whole soil transfers would display greater OTU richness and Shannon's diversity than commercial or control trees. Previous work in this system demonstrated that inoculation with whole soil transfers resulted in an increase in the number of terminal restriction fragments recovered in rhizosphere soils (Lance et al ). Our current approach implements HTS technology to further examine the influence of inoculation on soil fungal community structure and diversity.…”
Section: Introductionmentioning
confidence: 97%
“…litter transplants with the purpose of improving decomposition rates during restoration have not been attempted before (Box 1).Although the direct mechanisms by which whole-of-community rewilding improves ecosystem function is likely highly contextual, this practice can influence a broad range of functions, including; nutrient dynamics(Lance et al, 2019), plant growth(Emam, 2016),…”
mentioning
confidence: 99%
“…Therefore, planting a phylogenetically diverse tree restoration site could result in a more diverse fungal community. Future studies should measure ecosystem function (Lance et al, 2019), especially across a phylogenetic diversity gradient in tree restoration.…”
Section: Root and Rhizosphere Fungal Diversity Or Community Compositimentioning
confidence: 99%
“…Practitioners looking to collect soils for use as an inoculant could either avoid collecting from mature conspecific individuals if pathogens are found to have a primary influence on tree survivorship and growth (e.g., Packer and Clay, 2000), or conversely, target mature conspecific individuals if specific mutualisms elicit improved tree performance (e.g., den Bakker et al, 2004;Ishida et al, 2007). Plant-soil feedbacks that result from the conditioning of soil communities by different focal tree species have a profound influence on the microbial composition of forest soil transfers and the subsequent response of plants to inoculation during restoration (Wubs et al, 2016;Lance et al, 2019). Understanding the factors that influence the development of plant-soil feedbacks is essential to developing best practices for soil microbial community manipulation and is critical for ecological restoration of temperate forest communities.…”
Section: Introductionmentioning
confidence: 99%